أثر الشمول المالي على الفقر في الجزائر – دراسة قياسية خلال الفترة (1980-2019) (Journal of Economics and Management Research, 2023)
تهدف هذه الدراسة الى دراسة العلاقة بين مؤشرات الشمول المالي والمتمثلة في اجمالي القروض والودائع المصرفية، أقساط التأمينات على الفقر في الجزائر خلال الفترة من 1980 الى 2019 وهذا بالاعتماد على منهجية Gregory Hansen للتكامل المشترك ذي العتبات، خلصت الدراسة الى وجود علاقة طويلة الأجل بين متغيرات الدراسة بمقطع هيكلي سنة 1985. نتائج الأجل الطويل بينت وجود أثر معنوي إيجابي وسلبي للودائع المصرفية وأقساط التأمينات على الفقر تواليا أما القروض المصرفية لم يكن لها أي أثر معنوي، أما نتائج الأجل القصير فانه يوجد أثر معنوي سلبي وايجابي للقروض المصرفية وأقساط التأمينات على الفقر توالي أما الودائع المصرفية لم يكن لها أي أثر معنوي. Abstract: This study aims to study the relationship between financial inclusion indicators represented in total loans and bank deposits, insurance premiums on poverty in Algeria in the period from 1980 to 2019, This is based on Gregory Hansen’s methodology for joint integration with thresholds, the study concluded that there is a long-term relationship between variables of the study with a structural section in 1985. the long-term results showed a positive and negative significant effect of bank deposits and insurance premiums on poverty. As for bank loans, they did not have any significant effect. Concerning the short-term results, there is a significant negative and positive impact of bank loans and insurance premiums on poverty, respectively. Bank deposits had no significant effect.